MODERN MARKERS OF RHEUMATIC AND AUTOIMMUNE DISEASES - Djabbarova N.R.; Daminov F.A.; Yaxshimuradova S.; Sattorov Z. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Autoimmune diseases (AID) are not just one pathology but a class of health disorders characterized by the loss of tolerance to one’s own antigens. The exact mechanisms of their origin are unclear, but many internal and external factors act as triggers. Autoantibodies damage organs and systems by targeting autoantigens-substances from the body’s own cells recognized as foreign by the immune system [1,2,3].